Do socio-economic determinants affect residential fire-related injuries and deaths among Canadian children?. (18th May 2018) - Beaulieu, Emile; Zheng, Alex; Smith, Jennifer; Pike, Ian
Abstract: BACKGROUND: Fire is a leading cause of unintentional injuries among children in Canada. More specifically, residential fires are responsible for too many preventable deaths and injuries. Yet, there is no national database that reports on residential fire-related injuries and deaths among children. Although socio-economic determinants (SED) have been associated with increased risk of residential fire in the USA and UK, little is known about the significance of this impact on the Canadian child population. OBJECTIVES: This study examined the role of SED (low education, median income and average number of persons per dwelling (ANPD)) in residential fire-related injuries and deaths, and assessed the relationship between age and the severity of residential fire-related injuries and deaths, among children and youth in Canada. DESIGN/METHODS: A cross-sectional study design was used to examine data from the National Fire Information Database (NFID), which includes 10-years (2005–2015) of microdata information on fire incidents and losses reported by provincial/territorial Fire Marshals and Fire Commissioners Offices across Canada. Census 2011 data at the CSD level, from Statistics Canada, provided the SED variables. Our outcome of interest was the odds of death and major injury over minor injury. A logistic regression model was applied to test the relationship between age and SED with our outcome of interest, while adjusting for province. RESULTS: For every 1 person increase in the average ANPD at the CSD level, there is a 31% decrease in the odds of dying or being severely injured in a residential fire (p=0.0003). For every 1% increase in CSD's low education proportion, there is a 2.5% increase in the odds of dying or being severely injured in a residential fire (p=0.0002). Median income was not significantly associated with the odds of death and major injury over minor injury. The odds of death and major injury were not significantly different for youths and adults, compared to children, controlling for ANDP, low education and median income. CONCLUSION: The National Fire Information Database is one of the first to amass reliable fire incident and loss information across Canada into one database. Using this novel dataset, we determined that increased ANPD strongly decreased the odds of death and major injury over minor injury. Thus, the number of persons living in a household should be considered when targeting vulnerable children and youth for residential fire prevention and safety promotion programs.